The Story of an African Farm - Schreiner, Olive, 1855-1920 (Salt Lake City, UT : Project Gutenberg, 1998)
"The Story of an African Farm" by Olive Schreiner is a novel published in 1883. Set on a Karoo farm in 19th-century South Africa, it follows three characters$1 (BWaldo, Em, and Lyndall$1 (Bfrom childhood into adulthood. The novel explores profound questions about faith, feminism, love, marriage, and motherhood through its semi-autobiographical protagonists. Lyndall's fierce independence and refusal to conform to societal expectations anchor this groundbreaking work, which challenged Victorian conventions with its frank treatment of free thought, gender equality, and women's autonomy. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Story_of_an_African_Farm
Release date is 1998-09-01
Produced by Sue Asscher, and David Widger
Keywords: Historical fiction; Young women -- Fiction; Bildungsromans; Farm life -- Fiction; Feminists -- Fiction; Africa, Southern -- Fiction